"A Safe Way to Explore": Reframing Risk on the Internet Amidst Young Gay Men's Search for Identity. (July 2013) - Pingel, Emily S.; Bauermeister, Jose A.; Johns, Michelle M.; Eisenberg, Anna; Leslie-Santana, Matthew
Internet use provides a vital opportunity for sexual-minority youth to learn about sexual desires and pursue partnerships otherwise publically stigmatized. Researchers, however, have portrayed the Internet as an inherently risky venue for HIV or sexually transmitted infection (STI) transmission among young gay men (YGM). We therefore investigated how YGM use the Internet during adolescence and emerging adulthood. In the course of 34 in-depth, semistructured interviews with a sample of self-identified YGM, 18 to 24 years of age, we inquired about initial experiences of online dating. We found that YGM benefit online through exploration of their sexual identities, while simultaneously encountering and negotiating sources of risk. In examining YGM's perceptions of risk, we hope to reach a greater understanding of the opportunities for HIV prevention and health promotion among YGM.